Sociocultural Factors That Impact the Health Status, Quality of Life, and Academic Achievement of International Graduate Students: A Comprehensive Literature Review - Yunusa Vakkai, Roseline Jindori; Harris, Karleah; Crabbe, Jordan Jimmy; Chaplin, Kenneth Sean; Reynolds, Mara (Journal of International Students, 2020)
This literature review explores the sociocultural experiences of international graduate students in universities in the United States. In addition to the typical challenges faced by students going to universities in America, international graduate students undergo extra stress. Research has shown that students face issues such as negotiating the U.S. health care system, the pressures of competency in American English, balancing financial concerns, social connectivity, and anxiety due to isolation from family and friends. These factors place students at risk for developing health problems. Significant findings have indicated that institutions and students’ age play important roles in impacting students’ successful adjusting experiences even though the struggle for acculturation is a personal task. We organized our analysis and discussion around how to help graduate students to obtain sociocultural support and concluded with some suggestions on ways to address inadequacies within the institutional systems to make the schools welcoming for international students.